Strategi Pembelajaran Menyimak - Hamid, Abdul Hamid (Universitas Islam Negeri Raden Intan Lampung, 2015)
Listening competence is a kind of language competence and it is receptive in essence. Listening competence was firstly recognized officially as a main subject in foreign language teaching in 1970 and was begun by the birth of the theory of Total PsysicalResponse (TPS) of James Asher, The Natural Approach, and Silent Period. Learning strategy is an art of designing all learning activities in the classroom. Language learning strategy is teacher’s activities concerning his/her lesson plan; and listening learning strategy is an art of designing all learning activities in the classroom for improving students’ listening competence: students’ competences to re-inform their understanding through both speaking and writing’s competences. This article tries to elaborate several key issues about the definition of listening, its learning objectives and listening learning process, learning strategy and evaluation in the end of the class as well.